KONSEP PENDIDIKAN KARAKTER DALAM PERSPEKTIF FILSAFAT ETIKA IBNU MISKAWAIH: KELEMAHAN, RELEVANSI, DAN REKONSTRUKSI KONSEPTUAL - A.Dini Jumriana Adha; Nurul Fadlilah; Arif Mahfudhi (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
Character education has become an urgent necessity in today's education system, which is facing a moral crisis, a decline in values, and changes brought about by technology. One important ethical approach that needs to be revisited is the thinking of Ibn Miskawaih, a classical Islamic philosopher who offers a framework for moral education based on rationality and character development. The purpose of this article is to examine the concept of character education through the lens of ethical philosophy proposed by Ibn Miskawaih, assess its weaknesses, and formulate a new conceptual construct to remain relevant to the educational context of the 21st century. Through literature review and critical analysis, it was found that Miskawaih's ethics are based on four main pillars: self-control, courage, wisdom, and justice. However, there are contextual limitations that require these values to be reformulated to align with social changes, the digital education era, and modern psychological approaches. This article proposes the integration of classical ethical values with contemporary pedagogy, digital technology, and developmental psychology approaches to create a comprehensive, contextual, and practical character education.